catena-Poly[[iodidocopper(I)]-μ-4,4′,6,6′-tetramethyl-2,2′-(ethylenedithio)dipyrimidine-κ(2) N:N′] - Lu, Hong Bo (International Union of Crystallography, 2009)
In the title coordination polymer, [CuI(C(14)H(18)N(4)S(2))](n), the Cu(I) center is trigonally coordinated by two pyrimidine N-atom donors from two distinct dithioether ligands and one iodide anion. The Cu and I atoms are located on a twofold axis, whereas the midpoint of the central C—C bond of the dithioether ligand is located on an inversion center. Each organic ligand, acting in a bidentate mode, bridges two Cu(I )ions, resulting in the formation of polymeric zigzag chains. The dihedral angle between the two pyrimidine units bonded to the metal center is 88.01 (2)°. The crystal packing is mainly stabilized by van der Waals forces and π–π stacking interactions, with an interplanar distance between the pyrimidine rings of adjacent chains of 3.638 (3) Å.